2023
DOI: 10.3390/ijms24044178
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers in Connective Tissue Disease-Associated Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening complication of connective tissue diseases (CTDs) characterised by increased pulmonary arterial pressure and pulmonary vascular resistance. CTD-PAH is the result of a complex interplay among endothelial dysfunction and vascular remodelling, autoimmunity and inflammatory changes, ultimately leading to right heart dysfunction and failure. Due to the non-specific nature of the early symptoms and the lack of consensus on screening strategies—except for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 171 publications
(197 reference statements)
0
11
0
Order By: Relevance
“…The REVEAL registry study in the United States revealed that CTD-related PAH accounts for 25.3% of all PAH patients. SLE and systemic sclerosis (SSc) are the most common CTDs associated with PAH [11]. An analysis of the causes of death in SLE patients in China over the past 30 years found that SLE-PAH is the third leading cause of death in SLE patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…The REVEAL registry study in the United States revealed that CTD-related PAH accounts for 25.3% of all PAH patients. SLE and systemic sclerosis (SSc) are the most common CTDs associated with PAH [11]. An analysis of the causes of death in SLE patients in China over the past 30 years found that SLE-PAH is the third leading cause of death in SLE patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with SSc should be screened for PAH, even if asymptomatic, by cardiac echocolordoppler, respiratory testing, and NT-ProBNP assay. Diagnostic algorithms have been proposed to identify patients for RHC, which is still the gold standard tool for diagnosing PAH and PH [116][117][118][119][120][121][122][123][124][125][126]. Risk factors for PAH include severe Raynaud's phenomenon, severe digital ischemia, cutaneous telangiectasias, chronic disease, late onset of the disease, advanced age, postmenopausal status, reduced diffusing capacity (DLCO < 50%), DLCO/alveolar volume less than 70%, forced vital capacity/DLCO less than 1.6, and increased right ventricular systolic pressure greater than 2 mmHg/year [110][111][112][113][114][115][116][117][118][119].…”
Section: Biomarkers In Systemic Sclerosis Vascular Injury Focus On Pu...mentioning
confidence: 99%
“…Screening should include specific autoantibodies (anti-topoisomerase I (SCL-70), an-ticentromere and anti-RNA polymerase III and antiphospholipid antibodies), pulmonary function tests, echocardiography, pro-terminal brain natriuretic peptide (NT-proBNP), capillaroscopy of nail folds and initial high-resolution CT scan to rule out ILD, and, in case of PAH, right heart catheterization to determine PA pressure [118][119][120][121][122][123][124][125][126]151]. Many molecules have been associated with vascular complications of SSc, so there are many potential biomarkers for vascular disease and PAH in SSc.…”
Section: Biomarkers In Systemic Sclerosis Vascular Injury Focus On Pu...mentioning
confidence: 99%
See 2 more Smart Citations